The role of electoral and party systems in the development of fiscal institutions in the Central and Eastern European countries - Sami Yläoutinen (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
The literature on fiscal institutions has established a connection between the design of fiscal institutions and a country's political fundamentals. The paper includes a review of the party and electoral systems in the Central and Eastern European countries (the CEECs) and then reaches conclusions on what modes of fiscal governance (“commitment”, “delegation”, “fiefdom”) these countries should have developed based on their political fundamentals. Two major conclusions stand out. First, all of the countries have multi-dimensional social cleavage space which, together with the dominance of proportional electoral systems, suggests diverse party systems. This is a recipe for multi-party governments. Indeed, coalition governments have been dominant in the CEECs suggesting in turn that the majority of these countries should be leaning towards commitment approach. Second, the collapse of communism and consequent social changes led rather unsurprisingly to a certain political turmoil. This was evident especially during the first half of the 1990s. Some countries were affected more than others. Party structures have been in a constant change and reforms in the electoral laws have not been uncommon resulting in some countries to frequent shifts between different government types. This suggests that these countries have not been able to develop a coherent way to tackle the common pool resource problem. The reality largely confirms these expectations. The results therefore indicate that no “onesize- fits-all” solutions exist in fiscal management. Consequently, the design of such institutions should pay due attention to the political factors, alongside with the economic ones. The results indicate further that a certain degree of political stability is a prerequisite for stable fiscal conditions.
Keywords: 330; Finanzverfassung; Wahlsystem; Parteiensystem; Osteuropa; Politische Stabilität